Advances in the Prevention and Treatment of Obesity-Driven Effects in Breast Cancers - Chen, Kuo; Zhang, Jin; Beeraka, Narasimha M.; Tang, Chengyun; Babayeva, Yulia V.; Sinelnikov, Mikhail Y.; Zhang, Xinliang; Zhang, Jiacheng; Liu, Junqi; Reshetov, Igor V.; Sukocheva, Olga A.; Lu, Pengwei; et al. (Frontiers in Oncology, 2022)
Obesity and associated chronic inflammation were shown to facilitate breast cancer (BC) growth and metastasis. Leptin, adiponectin, estrogens, and several pro-inflammatory cytokines are involved in development of obesity-driven BCs through the activation of multiple oncogenic and pro-inflammatory pathways. The aim of this study was to assess the reported mechanisms of obesity-induced breast carcinogenesis and effectiveness of conventional & complementary BC therapies. We screened published original articles, reviews and meta-analyses that addressed the involvement of obesity-related signaling mechanisms in the BC development, BC treatment/prevention approaches, and post-treatment complications. PubMed, Medline, eMedicine, National Library of Medicine (NLM), and ReleMed databases were used to retrieve relevant studies using a set of keywords, including ‘obesity’, ‘oncogenic signaling pathways’, ‘inflammation’, ‘surgery’, ‘radiotherapy’, ‘conventional therapies’, and ‘diet’. Multiple studies indicated that effective BC treatment requires involvement of diet and exercise-based approaches in obese postmenopausal women. Furthermore, active lifestyle and diet-related interventions improved the patients’ overall quality of life and minimized adverse side effects after traditional BC treatment, including postsurgical lymphedema, post-chemo nausea, vomiting, and fatigue. Further investigation of beneficial effects of diet and physical activity may help to improve obesity-linked cancer therapies.